ANALISIS PELAKSANAAN FUNGSI MANAJEMEN TERHADAP PENINGKATAN MUTU PEMBELAJARAN PADA SMP NEGERI 27 MAKASSAR - Ahmad Musseng (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
The purpose of this study was to determine and analyze the influence of the learning management functions to increase the quality of learning as a result of learning in SMPN 27 Makassar, as well as to determine the factors that most influence on the improvement of the quality of learning. The research was conducted in SMP Negeri 27 Makassar. The study population numbered 59 teachers, both permanent teachers and teacher aides. Because populations are small, then the entire population sampled (sample of 100 per cent). The analytical tool used is descriptive quantitative analysis with multiple linear regression. The results showed that the application of the management function of a positive and significant effect, either simultaneously or partially to the increase in the quality of learning at SMPN 27 Makassar with the level of prediction (R square) of 0.758 (75.8 percent). With a high level of R square perencenaan shown that variable (X1), organizing (X2), the mobilization / leadership (X3), and monitoring / evaluation (X4) together have a strong influence on the improvement of the quality of learning in SMPN 27 Makassar